Monitoring Activity of Spodoptera frugiperda (Smith) in Different Areas of Maize Crops and Its Pesticide Susceptibility Testing Under Controlled Conditions - Alia Tajdar; Chuan Cao; Khalid Abbas; Muhammad Shah Zaib; Hafiz Muhammad Safeer; Syed Muhammad Zaka; Wangpeng Shi; Waqar Jaleel (Journal of Toxicology)
Fall armyworm (FAW), Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), is a polyphagous pest, particularly destructive to maize crops all over the world. It is native to America but has strong flying capabilities, and currently, the FAW has invaded many Asian countries, including Pakistan. Therefore, the current study aims to monitor its activity in four different areas of Pakistan. The damage percentage was recorded in different fields of maize crops caused by FAW. Furthermore, the susceptibility test of four different pesticides was performed against FAW under laboratory conditions. Maximum damage was recorded in the autumn crops that were surrounded by other alternative hosts such as sorghum, potato, jantar, rice chilies, and cotton when compared to the spring crops (with no alternate host in their surroundings). Temperature seems to play an important role in the size of the FAW population and the damage they cause. The results showed that among the four tested insecticides, emamectin benzoate and lufenuron exhibited higher toxic effects, while chlorpyrifos and lambda-cyhalothrin showed lower toxicities against FAW. Additionally, the study revealed an increasing resistance of FAW populations to commonly used insecticides, especially in South Punjab. These findings underscore the urgent need for integrated pest management strategies to address resistance development. Despite the observed resistance, emamectin benzoate remains a viable control option, but proactive resistance management is crucial for its continued effectiveness in long-term FAW control.